Relationship between Exclusive Breastfeeding and Stunting in Children Under Five: Critical Review - Putri Lutffiah Islamiyati; M Mutalazimah; M Muwakhidah; Zulia Setiyaningrum (Prosiding University Research Colloquium, 2022)
Prevalence of stunting in children under five in the world in 2019, which was 23.1% and in Indonesia in 2018, which was 30.8%. Exclusive breastfeeding is one of the factors that causes stunting in children under five. Breast milk contains nutrients that are in accordance with the growth and development of toddlers which can prevent stunting in children under five. This critical review design was aimed to review the articles related to exclusive breastfeeding and stunting in children under five. Articles were searched using the Google Scholar database source with a publication year of at least the last 10 years from national repute journal indexed by SINTA. This study reviewed 10 articles related to exclusive breastfeeding and stunting in children under five. This study found that most of the articles (7 articles) were showed a relationship between exclusive breastfeeding and stunting in children under five. According to these results, it is necessary to carry out promotive and preventive activities in the form of education related to exclusive breastfeeding to prevent and reduce the percentage of stunting in children under five.